2014
DOI: 10.1167/iovs.13-13310
|View full text |Cite
|
Sign up to set email alerts
|

Automated Segmentation of Optic Nerve Head Structures With Optical Coherence Tomography

Abstract: In individual scans, the median difference in ILM and BMO segmentations was <2 and <3 image pixels, respectively. There were no differences between patients and controls in ΔBMO-MRW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…A recent work by Almobarak et al. () on automated segmentation accuracy showed that mean BMO segmentation error was around 12 μ m; however, there were some cases in which this error was significantly higher. In our work, we also observed in the interobserver analysis a few cases with high BMO area variability (see outliers in Fig.…”
Section: Discussionmentioning
confidence: 94%
“…A recent work by Almobarak et al. () on automated segmentation accuracy showed that mean BMO segmentation error was around 12 μ m; however, there were some cases in which this error was significantly higher. In our work, we also observed in the interobserver analysis a few cases with high BMO area variability (see outliers in Fig.…”
Section: Discussionmentioning
confidence: 94%
“…The BMO minimum rim width (BMO-MRW) is now defined as a new parameter for the diagnosis of glaucoma. Determining MRW in this way is said to result in the most geometrically accurate measurement compared to scanning methods that have been in use since the introduction of OCT. 7,14 Kook et al 5 reported that in the ONH, BMO-MRW represents the outer margin of the neuroretinal rim and is an anatomically definitive structure that allows neuroretinal rim measurements. When making measurements with standard OCT devices, the optic disc margins are determined by clinical estimation, which is very error-prone (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Current segmentation approaches include the blood vessels as part of the ILM surface which increase the possibility of inaccurate measurement of the structural parameters such as BMO-MRW. The correct way of dealing with retinal blood vessels is controversial [21], however, we currently argue that doing a better job of only including the non-vascular tissue can provide the most precise measurements of glaucoma parameters of interest such as BMO-MRW, where going around the vessels would lead to overestimating the MRW. Note that as BMO-MRW is measured as the shortest Euclidean distance from the BMO to the ILM surface, depending on the location of blood vessels, and the closest point on the ILM surface to BMO, the BMO-MRW parameter may or may not be affected by the presence of blood vessel.…”
Section: Discussionmentioning
confidence: 99%